Assessment of geothermal resource potential in Changbaishan utilizing high-precision gravity-based man-machine interactive inversion technology - Xu, Zhi-He; Jiang, Ji-Yi; Gu, Guan-Wen; Sun, Zhen-Jun; Jiao, Xuan-Kai; Niu, Xing-Guo; Yu, Qin (Frontiers in Big Data, 2023)
As one of the clean energy sources, geothermal resources have no negative impact in changing the climate. However, the accurate assessment and precise identification of the potential geothermal resource is still complex and dynamic. In this paper, ~2,000 large-scale high-precision gravity survey points are conducted in the north of the Tianchi caldera, Changbaishan. Advanced data processing technologies can provide straightforward information on deep geothermal resources (Hot source, caprock, geothermal reservoir and geothermal migration pathway). Upwards continuation and the technologies decode two dome shaped low and gentle anomalies (−48 × 10−5 m/s2−65 m/s2) and a positive gravity gradient anomaly (0.4 × 10−7 m/s2−1.6 × 10−5 m/s2) in large-scale high-precision gravity planar. According to two point five dimensional man-machine interactive inversion technology and the research on petrophysical parameters, the density of the shied-forming basalts in the two orthogonal gravity sections is 2.58 g/cm3. The relatively intermediate to high density (2.60–2.75 g/cm3) represents geothermal reservoir, and low density (low to 2.58 g/cm3) is the geothermal migration pathway. In addition, large-scale high-precision gravity planar with a solution of about 1/50,000 indicate that the north of the Tianchi caldera exits the sedimentary basin and uplift mountain geothermal system.